The impact of epiretinal membrane stage and postoperative treatment on visual and anatomical outcomes following vitrectomy in eyes with preexisting macular edema - Efstathios Vounotrypidis; Julie Meyer; Denise Vogt; Christian Wertheimer; Tina Herold; Siegfried Priglinger; Armin Wolf (International Journal of Retina and Vitreous)
Abstract Backround Idiopathic epiretinal membrane (iERM) is often associated with different types of macular edema (ME). This study aimed to evaluate the impact of iERM stage and postoperative treatment on visual and anatomical outcomes after pars plana vitrectomy (PPV) with peeling in eyes with iERM and treatment-naïve pre-existing ME. Methods This retrospective analysis included eyes with iERM and different preexisting ME (microcystic = MME, cystoid = CME or combined ME) that underwent PPV with iERM and ILM-peeling and were followed for 12 months. Various OCT parameters, including central foveal thickness (CRT), outer nuclear layer (ONL) thickness, ectopic inner foveal layer (EIFL) thickness, presence of subretinal fluid, ellipsoid zone defects and central bouquet abnormalities were evaluated for their correlation with visual outcomes. Standard escalating postoperative treatment was steroids, adjuvant non-steroidal anti-inflammatory eye drops, adjuvant parabulbous injection (40 mg triamcinolone), intravitreal injection of long-lasting dexamethasone implant. Results Fifty eyes of 50 patients with iERM (stages 2–4) and MME (n = 20), CME (n = 15) or combined ME (n = 15) were included. Baseline BCVA was better in lower iERM stages (p = 0.011), showed no significant differences at 12 months (p = 0.379) and depended on underlying ME (p < 0.001). Worse final BCVA was associated with older age (Odds ratio [OR], 1.292; p = 0.001), need for treatment with intravitreal injection according to the standard escalating treatment schema (OR: 1.230; p = 0.007), preoperative EIFL > 100 μm (OR: 1.305; p < 0.001) and preoperative CRT < 450 μm (OR: 1.164; p = 0.048). Conclusions Baseline BCVA varied depending on pre-existing ME and iERM stage. Final BCVA was similar across all iERM stages but poorer in eyes with combined ME. Older age, preoperative EIFL > 100 μm, and need for treatment with intravitreal injection were associated with worse final BCVA. Trial registration The study was approved by the Institutional Review Board and the Ethics Committee of the Ludwig-Maximilian-University, Munich (Ethics Votum: 19/624) and adhered to the tenets of the Declaration of Helsinki.